Optimizing SIMBG to Strengthen Licensing Governance in Sinjai Regency - sumardi sumardi; Aliffia Nur Azizah; Ashar Abdillah (STISIPOL Raja Haji, 2026)
This research is driven by empirical evidence showing inconsistent utilization and declining effectiveness of SIMBG at the DPMPTSP of Sinjai Regency, as reflected in fluctuating application trends and persistent institutional, technical, and public literacy constraints despite ongoing digitalization initiatives.This study aims to analyze the effectiveness of the implementation of the Building Management Information System (SIMBG) at the Department of Investment and One-Stop Integrated Services (DPMPTSP) of Sinjai Regency, with the central research problem stated explicitly as follows: Why has the implementation of SIMBG not yet achieved the expected level of effectiveness despite ongoing digitalization efforts? Using a qualitative approach, data were collected through interviews, observations, and document analysis. The findings indicate that SIMBG implementation has progressed from 2022 to 2024 but remains suboptimal, as reflected in fluctuating application numbersan increase in 2023 followed by a substantial decline in 2024. Five core factors influence its effectiveness: institutional capacity, human resource competence, digital infrastructure availability, interagency communication patterns, and public literacy and compliance. Several obstacles were identified, including unharmonized SOPs across institutions, limited operator skills, unstable internet connectivity, and low public understanding of PBG requirements. The study recommends strengthening institutional frameworks, improving human resource capacities, optimizing interagency coordination, implementing data-driven public education, and enforcing continuous monitoring and evaluation. Overall, the study contributes to advancing the discourse on digital licensing governance at the regional level, particularly in areas with infrastructural and administrative constraints.